2017
DOI: 10.1371/journal.pone.0164644
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Sequencing of Extracellular RNA from Human Plasma

Abstract: The presence and relative stability of extracellular RNAs (exRNAs) in biofluids has led to an emerging recognition of their promise as ‘liquid biopsies’ for diseases. Most prior studies on discovery of exRNAs as disease-specific biomarkers have focused on microRNAs (miRNAs) using technologies such as qRT-PCR and microarrays. The recent application of next-generation sequencing to discovery of exRNA biomarkers has revealed the presence of potential novel miRNAs as well as other RNA species such as tRNAs, snoRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 84 publications
6
56
0
Order By: Relevance
“…This holds true particularly for extracellular RNA, which bears additional challenges such as low concentrations, diminished RNA integrity and high variability between individuals. Indeed, recent publications have highlighted the impact of cell-free RNA extraction strategies on small RNA-Seq, reporting quantitative and qualitative differences in resulting sequencing libraries [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…This holds true particularly for extracellular RNA, which bears additional challenges such as low concentrations, diminished RNA integrity and high variability between individuals. Indeed, recent publications have highlighted the impact of cell-free RNA extraction strategies on small RNA-Seq, reporting quantitative and qualitative differences in resulting sequencing libraries [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…These efforts have begun to elucidate the complex composition of exRNA in blood (Freedman et al, 2016;Yeri et al, 2017;Godoy et al, 2018;Max et al, 2018). There have been indications of extracellular mRNA and lncRNA in some studies of plasma, but results have been inconsistent, with some profiling studies reporting a variable percentage of them and others not even reporting their presence (Huang et al, 2013;Koh et al, 2014;Freedman et al, 2016;Yuan et al, 2016;Danielson et al, 2017;Yeri et al, 2017;Godoy et al, 2018;Max et al, 2018). Moreover, these profiling studies have used a variety of methods to evaluate exRNA (e.g., microarrays and different methodologies for RNA-seq) which, not surprisingly, contributes to the variation in findings.…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, HTS has the advantage of using total read count rather than a few selected transcripts for normalization, yet this depends on the total efficiency of extraction . Additionally, qPCR abundance of miR‐100‐5p and ‐203a showed low expression and it has been reported that high sequencing depth is required to detect lowly expressed genes . Thus, it is possible that in the case of these low abundance miRNAs, sequencing at a depth of at least 20 million reads per library provided greater sensitivity than the qPCR technique used.…”
Section: Discussionmentioning
confidence: 99%
“…[76] Additionally, qPCR abundance of miR-100-5p and -203a showed low expression and it has been reported that high sequencing depth is required to detect lowly expressed genes. [77] Thus, it is possible that in the case of these low abundance miRNAs, sequencing at a depth of at least 20 million reads per library provided greater sensitivity than the qPCR technique used. It would have been ideal to further validate the mRNA expression findings at the level of the post-transcriptionally regulated target proteins; however, due to insufficient remaining PBMCs this was not possible.…”
Section: Discussionmentioning
confidence: 99%